Acute changes in cardiac dimensions, function, and longitudinal mechanics in healthy individuals with and without high-altitude induced pulmonary hypertension at 4559 m - Mereles, Derliz; Rudolph, Jens; Greiner, Sebastian; Aurich, Matthias; Frey, Norbert; Katus, Hugo; Bärtsch, Peter; Dehnert, Christoph (Echocardiography, 2024)
Background High-altitude pulmonary hypertension (HAPH) has a prevalence of approximately 10%. Changes in cardiac morphology and function at high altitude, compared to a population that does not develop HAPH are scarce. Methods Four hundred twenty-one subjects were screened in a hypoxic chamber inspiring a FiO2 = 12% for 2 h. In 33 subjects an exaggerated increase in systolic pulmonary artery pressure (sPAP) could be confirmed in two independent measurements. Twenty nine of these, and further 24 matched subjects without sPAP increase were examined at 4559 m by Doppler echocardiography including global longitudinal strain (GLS). Results SPAP increase was higher in HAPH subjects (∆ = 10.2 vs. ∆ = 32.0 mm Hg, p < .001). LV eccentricity index (∆ = .15 vs. ∆ = .31, p = .009) increased more in HAPH. D-shaped LV (0 [0%] vs. 30 [93.8%], p = .00001) could be observed only in the HAPH group, and only in those with a sPAP ≥50 mm Hg. LV-EF (∆ = 4.5 vs. ∆ = 6.7%, p = .24) increased in both groups. LV-GLS (∆ = 1.2 vs. ∆ = 1.1 -%, p = .60) increased slightly. RV end-diastolic (∆ = 2.20 vs. ∆ = 2.7 cm2, p = .36) and end-systolic area (∆ = 2.1 vs. ∆ = 2.7 cm2, p = .39), as well as RA end-systolic area index (∆ = −.9 vs. ∆ = .3 cm2/m2, p = .01) increased, RV-FAC (∆ = −2.9 vs. ∆ = −4.7%, p = .43) decreased, this was more pronounced in HAPH, RV-GLS (∆ = 1.6 vs. ∆ = −.7 -%, p = .17) showed marginal changes. Conclusions LV and LA dimensions decrease and left ventricular function increases at high-altitude in subjects with and without HAPH. RV and RA dimensions increase, and RV longitudinal strain increases or remains unchanged in subjects with HAPH. Changes are negligible in those without HAPH.
Zuerst veröffentlicht: 23. Februar 2024
Gesehen am 15.07.2024